2021
DOI: 10.3389/fgene.2021.743758
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Genetic Architecture of Two Complex, Stomata-Related Drought-Responsive Traits by High-Throughput Physiological Phenotyping and GWAS in Cowpea (Vigna. Unguiculata L. Walp)

Abstract: Drought is one of the most devasting and frequent abiotic stresses in agriculture. While many morphological, biochemical and physiological indicators are being used to quantify plant drought responses, stomatal control, and hence the transpiration and photosynthesis regulation through it, is of particular importance in marking the plant capacity of balancing stress response and yield. Due to the difficulties in simultaneous, large-scale measurement of stomatal traits such as sensitivity and speed of stomatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Chlorophyll content is an important parameter reflecting the photosynthetic capacity of crops [73,74]. Net photosynthetic rate (Pn) reflects the plant photosynthetic capacity [75] and stomatal conductance (Gs) is closely related to plant stress resistance [76]. The water content of soil or substrate is closely related to plant photosynthesis [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll content is an important parameter reflecting the photosynthetic capacity of crops [73,74]. Net photosynthetic rate (Pn) reflects the plant photosynthetic capacity [75] and stomatal conductance (Gs) is closely related to plant stress resistance [76]. The water content of soil or substrate is closely related to plant photosynthesis [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs with the threshold of logarithm of odds (LOD) ≥ 2.5 were defined as significant SNPs. According to the cowpea linkage disequilibrium (LD) decay distance (350 kb) [18], the two significant SNPs within a same LD decay block were considered to represent the same QTL.…”
Section: Gwas Analysismentioning
confidence: 99%
“…GWAS has been widely used in crops such as rice, corn, soybean and watermelon [16]. In cowpea, using the GWAS based on the Cowpea iSelect Consortium Array (Illumina, Inc., San Diego, CA, USA) containing 51,128 SNP markers, Xu et al (2017) [6] identified 72 SNPs associated with pod length, Lo et al (2018) [17] identified 17 SNPs for grain size and Wu et al (2021) [18] identified 30 SNPs loci for cowpea drought tolerance. The objective of this study was to screen the FW resistant accessions in Chinese cowpea germplasms and identified the genes/QTLs conferring FW resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, non-destructive plant imaging combined with destructive leaf sampling allowed deep analysis of salt resistance (Berger et al, 2012 ). By employing non-destructive physiology-based phenomics assay, drought responses such as stomatal closure of tomato, cowpea and pepper were precisely and continuously phenotyped (Berger et al, 2010 ; Xu et al, 2015 ; Halperin et al, 2017 ; Dalal et al, 2019 ; Wu et al, 2021 ). Even though the phenomics characterization of quality and safety traits in horticultural crops has still been rare to date, a wave of phenomics-based technological revolution on phenotyping of these traits is expected to come soon in the near future.…”
Section: Progress In Phenotyping Of Quality and Safety Traits In Hort...mentioning
confidence: 99%